Environment of development and children's spatial perception Contexto de desenvolvimento e a percepfaçatild;o espacial de crian ças - Krebs R.J.* (2011)
Structural changes in social contexts where children participate may influence the development of spatial perception. The aim of this children's was to investigate the contexts of development and spatial perception of children's, based on the Bioecological theory of Bronfenbrenner. The questionnaire of Machado (2008) was applied in 60 students. The results showed the preference for leisure place is related to physical structure, security, lack of autonomy of children, transportation and places frequented by parents. The spatial perception of children is related to places frequented by them as home, school and the neighborhood.